Muatan Higher Order Thinking Skills Pada Buku Teks Cerdas Cergas Berbahasa dan Bersastra Indonesia SMA/SMK Kelas X terbitan Kemdikbud - Rohimakumullah, M. Arsyat; Mukhlis, Muhammad (UIR Press, 2024)
21st century education provides a big challenge for students to have critical and creative thinking skills. One of the skills needed is higher order thinking skills. This study aims to determine and explain the content of Higher Order Thinking Skills in the Smart Cergas Textbook in Indonesian Language and Literature SMA/SMK Class X. The research method used is a descriptive method of content analysis with a qualitative approach. Data collection techniques used in this research are documentation, note, write, conclude. Data analysis techniques identify, classify, analyze, interpret, conclude. The results showed that HOTS load training was found to be 71% with categories (C4) 23.3%, (C5) 27.1%, and (C6) 20.5%. While the LOTS was found to be 29% in the cognitive aspect of understanding (C2). Based on the results of these calculations, it can be explained that the HOTS content in the Indonesian Language and Literature Smart Textbook for SMA/SMK Class X published by the Ministry of Education and Culture has met the criteria for training content in the HOTS category.